2018
DOI: 10.1123/jpah.2017-0179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on the P300 of Elderly With Alzheimer’s Disease

Abstract: Physical exercise decreases reaction time and suggests a recovery in cortical activity, whereas SG activities could probably facilitate information processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…According to the results obtained in these cognitive tests, the participants who practised sports activities, whether open ones such as basketball or tennis, or closed ones like swimming or jogging, did better than those whose physical activity was irregular and of low intensity. Similar research has been conducted in people with different neuropathologies such as multiple sclerosis (Motl et al 2015), Alzheimer's disease (Pedroso et al 2018) and Parkinson's disease (Fiorelli et al 2019). In these studies, the participants with greater aerobic capacity presented relatively large brain structures related to cognitive abilities (such as the hippocampus or the thalamus) (Motl et al 2015).…”
Section: Introductionmentioning
confidence: 70%
“…According to the results obtained in these cognitive tests, the participants who practised sports activities, whether open ones such as basketball or tennis, or closed ones like swimming or jogging, did better than those whose physical activity was irregular and of low intensity. Similar research has been conducted in people with different neuropathologies such as multiple sclerosis (Motl et al 2015), Alzheimer's disease (Pedroso et al 2018) and Parkinson's disease (Fiorelli et al 2019). In these studies, the participants with greater aerobic capacity presented relatively large brain structures related to cognitive abilities (such as the hippocampus or the thalamus) (Motl et al 2015).…”
Section: Introductionmentioning
confidence: 70%
“…Neural connectivity effects were measured using electro-encephalogram (EEG) readings in 5 studies (Amjad et al, 2019;Hong et al, 2017;Kim and Lee, 2018;Pedroso et al, 2018; j QUALITY IN AGEING AND OLDER ADULTS j Yerokhin et al, 2012). All studies reported improved EEG patterns/complexity, indicating improved neural connectivity; cognitive function was improved too, although improvements were only slight in the case of Hong et al (2017).…”
Section: Neural Connectivitymentioning
confidence: 99%
“…In the study by Pedroso et al (2018), while the physical activity intervention improved reaction time, the control group took part in a social activity, which also resulted in improved information processing. This was the only study that had a defined/explicit social activity for control participants, although other group activities (intervention or control) may have had an implicit social element.…”
Section: Neural Connectivitymentioning
confidence: 99%
“…During the physical exercises the reaction time decreases, this fact involving a recovery of cortical activity, compared to the SG activities that play a role in facilitating the processing of information (Pedroso, Cancela et al, 2018), in case they assimilate the information by stimulating the visual and auditory analysers though not only motor. The importance of the physical exercises in the hydric environment lies in the facility to execute the strokes specific to swimming due to floatability, which the body gains in the water, as well as due to the mechanic, thermic and chemic factors of the water.…”
Section: Introductionmentioning
confidence: 99%